2022
DOI: 10.1007/s13187-022-02182-8
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Quality of COVID-19 Internet Resources for Cancer Patients

Abstract: Cancer patients may face difficulty evaluating web-based COVID-19 resources in context with their cancer diagnosis. The purpose of this study is to systematically evaluate educational resources available for cancer patients seeking online information on COVID-19 and cancer. The term “COVID-19 and Cancer” was searched in Google and metasearch engines Yippy and Dogpile. After applying inclusion and exclusion criteria, the results from the 3 lists were systematically combined for a final ranked list. This list wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Recently, an analysis of information on COVID-19 and cancer for cancer patients revealed that only 37 of the 398 accessible online sources in English listed by Google, Yippy, and Dogpile addressed COVID-19 in the context of a cancer diagnosis or treatment. None of these sites had a recommended reading level for public health communication (< 6.0 on the Flesch-Kincaid scale), and only 24% cited references 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an analysis of information on COVID-19 and cancer for cancer patients revealed that only 37 of the 398 accessible online sources in English listed by Google, Yippy, and Dogpile addressed COVID-19 in the context of a cancer diagnosis or treatment. None of these sites had a recommended reading level for public health communication (< 6.0 on the Flesch-Kincaid scale), and only 24% cited references 27 .…”
Section: Discussionmentioning
confidence: 99%
“…2015) has iteratively been improved through application to topics including breast cancer, lung cancer, and COVID-19 and cancer. This systematic approach to evaluating objective video parameter information is now the third iteration of this tool used for this purpose 10,11,12 . Videos were reviewed in four broad domains (Figure 2): General Parameters, Video Source/Presentation, Coverage, and Accuracy/Biases.…”
Section: Video Characteristicsmentioning
confidence: 99%
“…Recentemente, uma análise de informações sobre a COVID-19 e câncer para pacientes com câncer revelou que apenas 37 das 398 fontes online acessíveis em inglês listadas pelo Google, Yippy, e Dogpile abordaram a COVID-19 no contexto de um diagnóstico ou tratamento de câncer. Nenhum desses sites tinha um nível de leitura recomendado para comunicação sobre saúde pública (< 6,0 da escala de escolaridade Flesch-Kincaid), e apenas 24% citaram referências 189 .…”
Section: Avaliação Dos Profissionais Da Oncologia Quanto Ao Conhecime...unclassified